Strict Liabilty for Environmental Damage Post the Work Creation Law - Aida Dewi (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2022)
This study aims to analyze the reduction of the meaning of the principle of strict liability in the Omnibuslaw Act which will have a significant impact on environmental law enforcement in Indonesia. Environmental law enforcement will revert back to law enforcement in the past. The research used is normative legal research, with a statute approach. The results of the study indicate that the Omnibus Law abolishes the element